Keputusan Pembelian Masker Spirulina Tiens Berdasarkan Gaya Hidup (Studi Pada Mahasiswa Universitas Trunojoyo Madura) - Misrotul Hasanah; Nurita Andriani (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine the effect of  lifestyle consisting of activities, interests, and opinions on purchasing decisions for Spirulina Tiens masks at Trunojoyo University Madura students. The research method used is a quantitative research approach. The sample in this study were students of Trunojoyo Madura University who had purchased and used Tiens Spirulina masks at least twice with the provision that they were only consumers or users, not as distributors or agents, totaling 100 respondents with a purpose sampling technique. Research locations: Handoko Nilam Permai housing estate Block Hi No.2 Bangkalan and Permata Indah housing Block F No.05 Bangkalan. The types and sources of data used are primary data and secondary data. Data collection method using questionnaires. Based on the results of the partial analysis, the results of the t-test indicate that activity does not partially influence the purchase decision of Spirulina Tiens masks, while interests and opinions partially have a significant positive effect on purchasing decisions of Spirulina Tiens masks. Simultaneously, lifestyle which consists of activities, interests, and opinions has a significant positive effect on purchasing decisions for Spirulina Tiens masks.